Impact of Antifungal Prophylaxis on Colonization and Azole Susceptibility of Candida Species - Mann, Paul A.; McNicholas, Paul M.; Chau, Andrew S.; Patel, Reena; Mendrick, Cara; Ullmann, Andrew J.; Cornely, Oliver A.; Patino, Hernando; Black, Todd A. (Antimicrobial Agents and Chemotherapy, 2009)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC